The Responses of The Islamic Higher Education Students Against The Interpretation of The Quranâ€™s Violent Verses and Hadith in Riau - Zarkasih; Niki Dian Permana; Aliff Nawi; Rian Vebrianto; Musa Thahir (Universitas Islam Negeri Madura, 2021)
The understanding of spiritual doctrine becomes the reason, and it causes an escalation in violence in the name of religion. Misinterpreting the Qur'an verses causes the doer to legalize the violence they do. This article presents the responses of Islamic higher education students in Riau Province and Riau Islands about the interpretation of violent verses in the Qurâ€™an and Hadith. The sample consisted of 251 students from UIN Sultan Syarif Kasim in Riau, STAIN Bengkalis, and STAIN Abdurrahman Saleh in Riau Islands using a random sampling technique. Using descriptive analysis, the studentsâ€™ responses against the interpretation of violent verses were categorized as fairly positive at 61%. It indicates that 39% of the students had a negative response. Hence, this study recommends the importance of efforts to â€œneutralizeâ€ the studentsâ€™ understanding of the three Islamic higher education in Riau to prevent their tendency to have harsh or even radical understanding and responses.